Temperature-Dependent Double-Step CO Occlusion of KCO under Moist Conditions - Hideyuki Chioyama; Hongchao Luo; Tomonori Ohba; Hirofumi Kanoh (Adsorption Science & Technology)
In this study, CO 2 occlusion of K 2 CO 3 was examined at different temperatures under moist conditions. The CO 2 occlusion rate increased with increasing temperatures, whereas the saturated occlusion amount decreased. The highest occlusion amount (i.e. 6.48 mmol·g −1 ) was obtained at 313 K. Results of X-ray powder diffraction analysis showed that the formation of bicarbonate as a result of the K 2 CO 3 decomposition with CO 2 and H 2 O involved two reactions with K 4 H 2 (CO 3 ) 3 ·1.5H 2 O as an intermediate. It was determined that the lower saturated occlusion amount at higher temperatures originated from the exothermic property of the second reaction. Because the equilibrium constant for the bicarbonate formation is smaller at higher temperatures, the reaction does not proceed as quickly or efficiently according to Le Châtelier's principle. Therefore, the CO 2 occlusion of K 2 CO 3 is suitable for the saturated occlusion amount at lower temperatures.